Modified composite light calcium carbonate as well as preparation method and application thereof
By improving the preparation method of light calcium carbonate, combining the use of dispersants and crystal form control agents, as well as the grinding and modification of ultrafine heavy calcium carbonate, the problems of poor dispersion and poor mechanical properties of modified composite light calcium carbonate are solved, better dispersion and mechanical properties are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411990748.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, the dispersion of modified composite light calcium carbonate is poor and is used in the problem of poor mechanical properties in natural rubber.
By mixing the lime emulsion slurry with water, and adding a dispersant and a crystal form control agent to react under a carbon dioxide atmosphere, a light calcium carbonate powder was obtained; at the same time, the calcite raw ore was ground by crushing and ring roll grinding, water and predispersant were added to beat, and grinding with a silicon source and spray-drying to obtain ultrafine heavy calcium carbonate powder. Finally, the two were mixed and modified to obtain the modified composite light calcium carbonate.
It improves the dispersion of light calcium carbonate in rubber, enhances its mechanical properties, reduces production costs, and improves the wear resistance of rubber products.
Smart Images

Figure BDA0005223597270000071 
Figure BDA0005223597270000081 
Figure BDA0005223597270000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional inorganic powders, and in particular to a modified composite light calcium carbonate and a preparation method and application thereof. Background Art
[0002] Natural rubber (NR) is easy to process, and its adhesive and mechanical properties are excellent. Calcium carbonate (CaCO3) has a wide source of raw materials, high whiteness, low pollution, large filling volume, and good mixing and processing performance. These two raw materials constitute a light-colored rubber compound system with a large amount of use in the rubber industry. However, the price of natural rubber is relatively high. In order to reduce the material cost, it is necessary to add low-cost inorganic fillers to reduce the rubber content while ensuring the various mechanical properties of the rubber. The addition of calcium carbonate can reduce the extrusion shrinkage of the rubber, improve the stiffness of the rubber, and improve the processing performance. Therefore, it is widely used in the rubber industry. According to different preparation methods, calcium carbonate can be divided into light calcium carbonate (referred to as light calcium) and heavy calcium carbonate (referred to as heavy calcium). Light calcium carbonate is synthesized by precipitation method. It is obtained by calcining, digesting with water, and carbonizing limestone. Its crystals are generally crystalline, orthorhombic and hexagonal. Under electron microscope observation, it can be seen that the calcium carbonate morphology can be roughly divided into needle-shaped, spherical, chain-shaped, cubic and other morphologies. Different morphologies determine different application scenarios. Chain calcium carbonate, spindle calcium carbonate and needle calcium carbonate are widely used in the papermaking and plastic industries, which are conducive to saving resources and reducing costs, and can replace some expensive additives. Ordinary heavy calcium carbonate is ground from limestone, marble and calcite, and mainly exists in the form of blocks with sharp angles. It is mainly used in plastic systems to fill and reduce costs, but a large amount of ordinary heavy calcium carbonate filling will cause a great loss of mechanical properties.
[0003] In the rubber industry, the amount of light calcium carbonate used is much greater than that of heavy calcium carbonate. The main reasons are: first, the regular crystal structure of light calcium carbonate has a certain reinforcing effect in the rubber system; second, heavy calcium carbonate with ordinary fineness (325 mesh) has coarse particles, which will affect the surface gloss and mechanical properties of the product when filled into downstream rubber products, so it is not widely used. However, due to the characteristics of its process, light calcium carbonate has problems such as high moisture content in the production process and poor dispersion in downstream product applications. It is easy to have problems such as bubbling and low mixing efficiency during the application process.
[0004] Based on this, it is very important that the present invention provides a modified composite light calcium carbonate with good dispersibility and which can be applied to natural rubber to improve mechanical properties. Summary of the invention
[0005] The purpose of the present invention is to provide a modified composite light calcium carbonate and a preparation method and application thereof, so as to solve the technical problems in the prior art that the modified composite light calcium carbonate has poor dispersibility and poor mechanical properties when used in natural rubber.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a modified composite light calcium carbonate, comprising the following steps:
[0008] (1) mixing lime milk slurry and water to obtain slurry, and then adding a dispersant and a crystal control agent to react under a carbon dioxide atmosphere to obtain light calcium carbonate powder;
[0009] (2) crushing the calcite ore and then grinding it by a roller mill to obtain a coarse calcium carbonate powder, then adding water and a part of the pre-dispersant to make a slurry to obtain a calcium carbonate slurry, then adding the remaining pre-dispersant and a silicon source to grind and spray dry in sequence to obtain an ultrafine heavy calcium carbonate powder;
[0010] (3) Light calcium carbonate powder, ultrafine heavy calcium carbonate powder and a composite modifier are mixed and modified to obtain a modified composite light calcium carbonate.
[0011] Furthermore, the mass ratio of the lime milk slurry to water is 1:0.5-2;
[0012] The amount of the dispersant added is 0.2-0.5% of the slurry mass;
[0013] The addition amount of the crystal form control agent is 0.3-0.6% of the slurry mass;
[0014] The flow rate of the carbon dioxide is 1.5 to 2.0 L / h.
[0015] Furthermore, the dispersant includes sodium polyacrylate and / or sodium hexametaphosphate, and the dispersant is added by continuous spraying;
[0016] The crystal form controlling agent includes at least two of glycerol, EDTA and sodium citrate.
[0017] Furthermore, in the step (1), the mixing is carried out under stirring, the stirring temperature is 50 to 60° C., and the stirring time is 30 to 40 minutes;
[0018] 30 minutes after the reaction started, the pH value of the slurry was tested every 5 minutes until the reaction was completed when the pH was between 7 and 8.
[0019] Furthermore, the calcium carbonate content in the calcite ore is ≥ 97%;
[0020] The particle size of the calcium carbonate coarse powder is 300-400 mesh;
[0021] The D97 of the ultrafine heavy calcium carbonate powder is 2 to 2.5 μm.
[0022] Furthermore, the solid content of the calcium carbonate slurry is 60-70%;
[0023] The amount of silicon source added is 20-30% of the mass of the calcium carbonate coarse powder;
[0024] The addition amount of the pre-dispersant is 0.5-0.8% of the mass of the calcium carbonate coarse powder, and the mass ratio of part of the pre-dispersant to the remaining pre-dispersant is 0.6-0.8:0.2-0.4.
[0025] Further, the pre-dispersant includes sodium alkyl diphenyl ether sulfonate and / or sodium fatty alcohol polyoxyethylene ether sulfate;
[0026] The silicon source is sodium silicate and / or potassium silicate.
[0027] Furthermore, the mass ratio of the light calcium carbonate powder to the ultrafine heavy calcium carbonate powder is 6-8:2-4;
[0028] The addition amount of the composite modifier accounts for 0.8-1.2% of the total mass of the light calcium carbonate powder and the ultrafine heavy calcium carbonate powder;
[0029] The composite modifier is obtained by compounding vinyl-terminated silicone oil and silane coupling agent KH560, wherein the addition amount of vinyl-terminated silicone oil is 0.5-0.8% of the total mass of light calcium carbonate powder and ultrafine heavy calcium carbonate powder, and the addition amount of silane coupling agent KH560 is 0.3-0.5% of the total mass of light calcium carbonate powder and ultrafine heavy calcium carbonate powder;
[0030] The modification temperature is 100-120° C., and the modification time is 30-50 minutes.
[0031] The invention provides a modified composite light calcium carbonate prepared by the preparation method.
[0032] The present invention also provides an application of the modified composite light calcium carbonate in the preparation of wear-resistant rubber. 100 parts of natural rubber, 3 to 7 parts of zinc oxide, 1 to 3 parts of stearic acid, 1 to 3 parts of sulfur, 1 to 3 parts of accelerator DM, 40 to 60 parts of the modified composite light calcium carbonate according to claim 9, 0.1 to 1 part of accelerator TMTD, 1 to 3 parts of silane coupling agent Si-69, 1 to 3 parts of plasticizer DOP, 1 to 5 parts of antioxidant RD, and 3 to 8 parts of white carbon black are mixed, and kneaded at 50 to 70° C. for 10 to 30 minutes to obtain the wear-resistant rubber.
[0033] Beneficial effects of the present invention:
[0034] (1) The modified composite light calcium carbonate produced by the present invention not only retains the regular crystal structure of light calcium carbonate, but also has the advantages of small particle size, high 2 μm content and large specific surface area of ultrafine heavy calcium carbonate, thereby solving the problem that the light calcium carbonate is generally high in water content in natural rubber due to process problems, resulting in poor dispersibility and great influence on mechanical properties, thereby improving the dispersibility of calcium carbonate in rubber and reducing production costs.
[0035] (2) In the production and preparation process of the light calcium carbonate in the modified composite light calcium carbonate produced by the present invention, a composite crystal control agent is used to make the crystal structure of the light calcium carbonate more regular. When applied to the natural rubber system, the mechanical properties of the natural rubber are greatly improved.
[0036] (3) The ultrafine heavy calcium carbonate in the modified composite light calcium carbonate produced by the present invention adopts a wet grinding process. During the grinding process, as the grinding time increases, the temperature of the slurry increases, and the general temperature can rise to 75-85°C. The silicon source added at this temperature can not only perform in-situ inorganic coating on the surface of calcium carbonate, but also can be used as a dispersant, further reducing the agglomeration of calcium carbonate during the grinding process, and greatly increasing the specific surface area of the ultrafine heavy calcium carbonate.
[0037] (4) The present invention uses a composite modifier such as silicone oil to modify the surface of the in-situ inorganically coated calcium carbonate, and the obtained calcium carbonate has good compatibility with rubber molecules, thereby improving the mechanical properties and wear resistance of the rubber product, especially the silicone rubber system. DETAILED DESCRIPTION
[0038] The present invention provides a method for preparing a modified composite light calcium carbonate, comprising the following steps:
[0039] (1) mixing lime milk slurry and water to obtain slurry, and then adding a dispersant and a crystal control agent to react under a carbon dioxide atmosphere to obtain light calcium carbonate powder;
[0040] (2) crushing the calcite ore and then grinding it by a roller mill to obtain a coarse calcium carbonate powder, then adding water and a part of the pre-dispersant to make a slurry to obtain a calcium carbonate slurry, then adding the remaining pre-dispersant and a silicon source to grind and spray dry in sequence to obtain an ultrafine heavy calcium carbonate powder;
[0041] (3) Light calcium carbonate powder, ultrafine heavy calcium carbonate powder and a composite modifier are mixed and modified to obtain a modified composite light calcium carbonate.
[0042] In the present invention, the mass ratio of the lime milk slurry to water is 1:0.5-2, preferably 1:0.7-1.8, and more preferably 1:1-1.5;
[0043] The amount of the dispersant added is 0.2-0.5% of the slurry mass, preferably 0.3-0.45%, and more preferably 0.4%;
[0044] The addition amount of the crystal form control agent is 0.3-0.6% of the mass of the slurry, preferably 0.35-0.55%, and more preferably 0.4-0.5%;
[0045] The flow rate of the carbon dioxide is 1.5 to 2.0 L / h, preferably 1.6 to 1.9 L / h, and more preferably 1.7 to 1.8 L / h.
[0046] In the present invention, the dispersant includes sodium polyacrylate and / or sodium hexametaphosphate, preferably sodium hexametaphosphate, and the dispersant is added by continuous spraying;
[0047] The crystal form controlling agent includes at least two of glycerol, EDTA and sodium citrate, preferably a mixture of glycerol and EDTA, a mixture of glycerol and sodium citrate or a mixture of EDTA and sodium citrate, and further preferably a mixture of glycerol and EDTA or a mixture of glycerol and sodium citrate.
[0048] In the present invention, in the step (1), the mixing is carried out under stirring, the stirring temperature is 50 to 60° C., preferably 52 to 58° C., and more preferably 54 to 56° C.; the stirring time is 30 to 40 min, preferably 32 to 38 min, and more preferably 34 to 36 min;
[0049] 30 minutes after the reaction started, the pH value of the slurry was tested every 5 minutes until the reaction was completed when the pH was between 7 and 8.
[0050] In the present invention, the calcium carbonate content in the calcite ore is ≥97%, preferably ≥97.2%, and more preferably ≥97.5%;
[0051] The particle size of the calcium carbonate coarse powder is 300-400 mesh, preferably 310-390 mesh, and more preferably 320-380 mesh;
[0052] The D97 of the ultrafine heavy calcium carbonate powder is 2 to 2.5 μm, preferably 2.1 to 2.4 μm, and more preferably 2.2 to 2.3 μm.
[0053] In the present invention, the solid content of the calcium carbonate slurry is 60-70%, preferably 62-68%, and more preferably 64-66%;
[0054] The amount of silicon source added is 20-30% of the mass of the calcium carbonate coarse powder, preferably 22-28%, and more preferably 24-26%;
[0055] The addition amount of the pre-dispersant is 0.5-0.8% of the mass of the calcium carbonate coarse powder, preferably 0.55-0.75%, and more preferably 0.6-0.7%; the mass ratio of part of the pre-dispersant and the remaining pre-dispersant is 0.6-0.8:0.2-0.4, preferably 0.65-0.75:0.25-0.35, and more preferably 0.7:0.3.
[0056] In the present invention, the pre-dispersant comprises sodium alkyl diphenyl ether sulfonate and / or sodium fatty alcohol polyoxyethylene ether sulfate, preferably sodium alkyl diphenyl ether sulfonate;
[0057] The silicon source is sodium silicate and / or potassium silicate, preferably sodium silicate.
[0058] In the present invention, the mass ratio of the light calcium carbonate powder to the ultrafine heavy calcium carbonate powder is 6-8:2-4, preferably 6.5-7.5:2.5-3.5, and more preferably 7:3;
[0059] The addition amount of the composite modifier accounts for 0.8-1.2% of the total mass of the light calcium carbonate powder and the ultrafine heavy calcium carbonate powder, preferably 0.9-1.1%, and more preferably 1%;
[0060] The composite modifier is obtained by compounding vinyl-terminated silicone oil and silane coupling agent KH560, wherein the addition amount of vinyl-terminated silicone oil is 0.5-0.8% of the total mass of light calcium carbonate powder and ultrafine heavy calcium carbonate powder, preferably 0.55-0.75%, and more preferably 0.6-0.7%; the addition amount of silane coupling agent KH560 is 0.3-0.5% of the total mass of light calcium carbonate powder and ultrafine heavy calcium carbonate powder, preferably 0.35-0.45%, and more preferably 0.4%;
[0061] The modification temperature is 100-120° C., preferably 105-115° C., and more preferably 110° C.; the modification time is 30-50 min, preferably 35-45 min, and more preferably 40 min.
[0062] The invention provides a modified composite light calcium carbonate prepared by the preparation method.
[0063] The present invention also provides an application of the modified composite light calcium carbonate in the preparation of wear-resistant rubber. 100 parts of natural rubber, 3 to 7 parts of zinc oxide, 1 to 3 parts of stearic acid, 1 to 3 parts of sulfur, 1 to 3 parts of accelerator DM, 40 to 60 parts of the modified composite light calcium carbonate according to claim 9, 0.1 to 1 part of accelerator TMTD, 1 to 3 parts of silane coupling agent Si-69, 1 to 3 parts of plasticizer DOP, 1 to 5 parts of antioxidant RD, and 3 to 8 parts of white carbon black are mixed, and kneaded at 50 to 70° C. for 10 to 30 minutes to obtain the wear-resistant rubber.
[0064] In the present invention, the content of zinc oxide is preferably 4 to 6 parts by weight, and more preferably 5 parts by weight.
[0065] In the present invention, the content of stearic acid is preferably 1.5 to 2.5 parts by weight, and more preferably 2 parts.
[0066] In the present invention, the content of sulfur is preferably 1.5 to 2.5 parts by weight, and more preferably 2 parts by weight.
[0067] In the present invention, the content of the accelerator DM is preferably 1.5 to 2.5 parts by weight, and more preferably 2 parts by weight.
[0068] In the present invention, the content of the modified composite light calcium carbonate is preferably 42 to 58 parts by weight, and more preferably 45 to 55 parts by weight.
[0069] In the present invention, the content of the accelerator TMTD is preferably 0.2 to 0.9 parts by weight, and more preferably 0.3 to 0.8 parts by weight.
[0070] In the present invention, the content of the silane coupling agent Si-69 is preferably 1.5 to 2.5 parts by weight, and more preferably 2 parts by weight.
[0071] In the present invention, the content of the plasticizer DOP is preferably 1.5 to 2.5 parts by weight, and more preferably 2 parts by weight.
[0072] In the present invention, the content of the antioxidant RD is preferably 1.5 to 4.5 parts by weight, and more preferably 2 to 4 parts by weight.
[0073] In the present invention, the content of the white carbon black is preferably 4 to 7 parts by weight, and more preferably 5 to 8 parts by weight.
[0074] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0075] Example 1
[0076] The lime milk slurry and water in a mass ratio of 1:1 were mixed at 55°C for 35 minutes to obtain a slurry with a solid content of 65%, and then 0.5% of sodium polyacrylate and 0.3% of glycerol and EDTA composite crystal control agent were added, wherein the mass ratio of glycerol to EDTA was 7:3, and then the reaction was carried out in a carbon dioxide atmosphere with a flow rate of 1.5L / h, and the pH value of the slurry was detected every 5 minutes after 30 minutes of the reaction process until the pH value was stopped at 7.5, at which time the carbonization reaction was completed, the liquid after the reaction was filtered and the filter residue was retained, and the filter residue was washed with distilled water for 3 times and then microwave dried to obtain light calcium carbonate powder; the calcite ore with a calcium carbonate content of ≥97% was crushed and dry-ground by a ring roller mill to obtain a 400-mesh calcium carbonate coarse powder, and then water and part of the sodium alkyl diphenyl ether sulfonate were added to beat slurry to obtain a calcium carbonate slurry with a solid content of 62%, then add the remaining sodium alkyl diphenyl oxide sulfonate and sodium silicate added in an amount of 20% of the mass of the calcium carbonate coarse powder, grind and spray dry in sequence to obtain an ultrafine heavy calcium carbonate powder with a D97 of 2 μm, the addition amount of the silicon source is 20% of the mass of the calcium carbonate coarse powder, the addition amount of the sodium alkyl diphenyl oxide sulfonate is 0.5% of the mass of the calcium carbonate coarse powder, and the mass ratio of part of the sodium alkyl diphenyl oxide sulfonate to the remaining sodium alkyl diphenyl oxide sulfonate is 0.7:0.3; light calcium carbonate powder and ultrafine heavy calcium carbonate powder in a mass ratio of 6:4 are mixed with a composite modifier of 0.5% of terminal vinyl silicone oil and 0.3% of KH560 added in an amount of the total mass of the light calcium carbonate powder and the ultrafine heavy calcium carbonate powder, and then modified, the modification temperature is 110°C, and the modification time is 40min to obtain a modified composite light calcium carbonate.
[0077] The modified composite light calcium carbonate prepared in Example 1 was subjected to batch sample testing, and the test results are shown in Table 1.
[0078] Table 1 Performance test results of the modified composite light calcium carbonate prepared in Example 1
[0079]
[0080]
[0081] 100 parts of natural rubber, 5 parts of zinc oxide, 2 parts of stearic acid, 2 parts of sulfur, 2 parts of accelerator DM, 50 parts of the modified composite light calcium carbonate prepared above, 0.5 parts of accelerator TMTD, 2 parts of Si-69, 2 parts of DOP, 3 parts of antioxidant RD, and 6 parts of white carbon black were mixed and kneaded at 60°C for 20 minutes to obtain a wear-resistant rubber.
[0082] Example 2
[0083] The lime milk slurry and water in a mass ratio of 1:1 were mixed at 55°C for 35 minutes to obtain a slurry with a solid content of 65%, and then 0.3% of sodium hexametaphosphate by mass and 0.4% of sodium citrate and EDTA composite crystal control agent by mass of the slurry were added, wherein the mass ratio of sodium citrate to EDTA was 6:4, and then the reaction was carried out in a carbon dioxide atmosphere with a flow rate of 1.5L / h, and the pH value of the slurry was detected every 5 minutes after 30 minutes of the reaction process until the pH value was stopped at 7.5, at which time the carbonization reaction was completed, the liquid after the reaction was filtered and the filter residue was retained, and the filter residue was washed with distilled water for 3 times and then microwave dried to obtain light calcium carbonate powder; the calcite ore with a calcium carbonate content of ≥97% was crushed and dry-ground by a ring roller mill to obtain a 400-mesh calcium carbonate coarse powder, and then water and part of fatty alcohol polyoxyethylene ether sodium sulfate were added to beat slurry to obtain a calcium carbonate slurry with a solid content of 65%, then add the remaining fatty alcohol polyoxyethylene ether sodium sulfate and sodium silicate added in an amount of 20% of the mass of the calcium carbonate coarse powder, grind and spray dry in sequence to obtain an ultrafine heavy calcium carbonate powder with a D97 of 2μm, the addition amount of the silicon source is 20% of the mass of the calcium carbonate coarse powder, the addition amount of the fatty alcohol polyoxyethylene ether sodium sulfate is 0.6% of the mass of the calcium carbonate coarse powder, and the mass ratio of part of the alkyl diphenyl ether sodium sulfonate to the remaining alkyl diphenyl ether sodium sulfonate is 0.8:0.2; light calcium carbonate powder and ultrafine heavy calcium carbonate powder in a mass ratio of 7:3 are mixed with a composite modifier of 0.6% of terminal vinyl silicone oil and 0.4% of KH560 added in an amount of the total mass of the light calcium carbonate powder and the ultrafine heavy calcium carbonate powder, and then modified, the modification temperature is 110°C, and the modification time is 40min to obtain a modified composite light calcium carbonate.
[0084] The modified composite light calcium carbonate prepared in Example 2 was subjected to batch sample testing, and the test results are shown in Table 2.
[0085] Table 2 Performance test results of the modified composite light calcium carbonate prepared in Example 2
[0086]
[0087] 100 parts of natural rubber, 5 parts of zinc oxide, 2 parts of stearic acid, 2 parts of sulfur, 2 parts of accelerator DM, 50 parts of the modified composite light calcium carbonate prepared above, 0.5 parts of accelerator TMTD, 2 parts of Si-69, 2 parts of DOP, 3 parts of antioxidant RD, and 6 parts of white carbon black were mixed and kneaded at 60°C for 20 minutes to obtain a wear-resistant rubber.
[0088] Example 3
[0089] The lime milk slurry and water in a mass ratio of 1:1 were mixed at 55°C for 35 minutes to obtain a slurry with a solid content of 65%, and then 0.5% of the mass of sodium polyacrylate and sodium hexametaphosphate were added, and the mass ratio of sodium polyacrylate and sodium hexametaphosphate was 7:3. 0.5% of the mass of glycerol and sodium citrate composite crystal control agent was added, wherein the mass ratio of glycerol and sodium citrate was 8:2, and then the reaction was carried out in a carbon dioxide atmosphere with a flow rate of 1.5L / h, and After 30 minutes of the reaction process, the pH value of the slurry is detected every 5 minutes until the pH value is 7.5, and the addition is stopped. At this time, the carbonization reaction is completed, the liquid after the reaction is filtered and the filter residue is retained, and the filter residue is washed with distilled water for 3 times and then microwave dried to obtain light calcium carbonate powder; the calcite ore with a calcium carbonate content of ≥97% is crushed and dry-ground by a ring roller mill to obtain a 400-mesh calcium carbonate coarse powder, and then water, part of sodium alkyl diphenyl ether sulfonate and part of fatty alcohol polyoxyethylene are added. Sodium sulfate is beaten to obtain a calcium carbonate slurry with a solid content of 69%, and then the remaining fatty alcohol polyoxyethylene ether sodium sulfate and sodium silicate added in an amount of 20% of the mass of the calcium carbonate coarse powder are added, and then ground and spray-dried in sequence to obtain an ultrafine heavy calcium carbonate powder with a D97 of 2 μm. The addition amount of the silicon source is 30% of the mass of the calcium carbonate coarse powder, the addition amount of the fatty alcohol polyoxyethylene ether sodium sulfate is 0.4% of the mass of the calcium carbonate coarse powder, and the mass ratio of the sodium alkyl diphenyl ether sulfonate to the sodium fatty alcohol polyoxyethylene sulfate is 2. The mass ratio of the alkyl diphenyl ether sodium sulfonate to the remaining alkyl diphenyl ether sodium sulfonate is 6:4, and the mass ratio of part of the alkyl diphenyl ether sodium sulfonate to the remaining alkyl diphenyl ether sodium sulfonate is 0.7:0.3; the light calcium carbonate powder and the ultrafine heavy calcium carbonate powder in a mass ratio of 8:2 are mixed with a composite modifier of 0.5% of terminal vinyl silicone oil and 0.5% of KH560 added in an amount accounting for the total mass of the light calcium carbonate powder and the ultrafine heavy calcium carbonate powder, and then modified. The modification temperature is 110°C and the modification time is 40min to obtain a modified composite light calcium carbonate.
[0090] The modified composite light calcium carbonate prepared in Example 3 was subjected to batch sample testing, and the test results are shown in Table 3.
[0091] Table 3 Performance test results of the modified composite light calcium carbonate prepared in Example 3
[0092]
[0093] 100 parts of natural rubber, 5 parts of zinc oxide, 2 parts of stearic acid, 2 parts of sulfur, 2 parts of accelerator DM, 50 parts of the modified composite light calcium carbonate prepared above, 0.5 parts of accelerator TMTD, 2 parts of Si-69, 2 parts of DOP, 3 parts of antioxidant RD, and 6 parts of white carbon black were mixed and kneaded at 60°C for 20 minutes to obtain a wear-resistant rubber.
[0094] Comparative Example 1
[0095] Compared with Example 1, the difference is that when preparing the wear-resistant rubber in Comparative Example 1, the modified composite light calcium carbonate prepared in Example 1 is replaced with ordinary light calcium carbonate.
[0096] Comparative Example 2
[0097] Compared with Example 1, the difference is that when preparing the wear-resistant rubber in Comparative Example 2, the modified composite light calcium carbonate prepared in Example 1 is replaced with ordinary heavy calcium carbonate.
[0098] The wear-resistant rubber prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested, and the determination of the tensile stress-strain properties of the rubber was tested in accordance with the national standard GB / T528-2009; the wear index of the rubber was determined using an Akron abrasion tester, and the determination method was carried out in accordance with the national standard GB / T1689-2014. The test results are shown in Table 4.
[0099] Table 4 Performance test results of wear-resistant rubber prepared in Examples 1 to 3 and Comparative Examples 1 to 2
[0100]
[0101] It can be seen from the above embodiments that the present invention provides a modified composite light calcium carbonate and a preparation method and application thereof. It can be seen from Tables 1 to 4 that the prepared modified composite light calcium carbonate is added to natural rubber, and a composite crystal control agent is used in the process of producing light calcium carbonate, so that the crystal structure of the light carbonate is more regular, and the application in the natural rubber system has a great improvement on the mechanical properties. At the same time, the inorganic silicon source used in the wet grinding process of ultrafine heavy calcium carbonate can not only be used as an in-situ inorganic coating, but also as a dispersant. At the same time, a pre-dispersant is added during the wet grinding process to obtain ultrafine heavy calcium carbonate with a small particle size, a large specific surface area and low moisture. After the two are compounded and modified with silicone oil, they can act as a lubricating powder particle, hinder the formation of a carbon black-carbon black network, increase the interaction between carbon black and rubber matrix, and greatly reduce the wear index of the rubber material. Under standard conditions, the lower the wear index, the better the wear resistance, and vice versa. The different modified composite light calcium carbonates obtained by changing the crystal form control agent and the ratio of the silicon source and the modifier in Examples 1 to 3 are significantly improved in mechanical properties and wear resistance compared to Example 1 in which ordinary light calcium carbonate is added and Example 2 in which ordinary heavy calcium carbonate is added, in the same formulation system, indicating that the modified composite light calcium carbonate prepared by the present invention has excellent performance when applied to natural rubber.
[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a modified composite light calcium carbonate, characterized in that: The following steps are involved: (1) mixing lime milk slurry and water to obtain slurry, and then adding a dispersant and a crystal control agent to react under a carbon dioxide atmosphere to obtain light calcium carbonate powder; (2) crushing the calcite ore and then grinding it by a roller mill to obtain a coarse calcium carbonate powder, then adding water and a part of the pre-dispersant to make a slurry to obtain a calcium carbonate slurry, then adding the remaining pre-dispersant and a silicon source to grind and spray dry in sequence to obtain an ultrafine heavy calcium carbonate powder; (3) Light calcium carbonate powder, ultrafine heavy calcium carbonate powder and a composite modifier are mixed and modified to obtain a modified composite light calcium carbonate.
2. The method for preparing the modified composite light calcium carbonate according to claim 1, characterized in that: The mass ratio of the lime milk slurry to water is 1:0.5-2; The amount of the dispersant added is 0.2-0.5% of the slurry mass; The addition amount of the crystal form control agent is 0.3-0.6% of the slurry mass; The flow rate of the carbon dioxide is 1.5 to 2.0 L / h.
3. The method for preparing the modified composite light calcium carbonate according to claim 1 or 2, characterized in that: The dispersant includes sodium polyacrylate and / or sodium hexametaphosphate, and the dispersant is added by continuous spraying; The crystal form controlling agent includes at least two of glycerol, EDTA and sodium citrate.
4. The method for preparing the modified composite light calcium carbonate according to claim 3, characterized in that: In the step (1), the mixing is carried out under stirring, the stirring temperature is 50 to 60° C., and the stirring time is 30 to 40 minutes; 30 minutes after the reaction started, the pH value of the slurry was tested every 5 minutes until the reaction was completed when the pH was between 7 and 8.
5. The method for preparing the modified composite light calcium carbonate according to claim 1, 2 or 4, characterized in that: The calcium carbonate content in the calcite ore is ≥ 97%; The particle size of the calcium carbonate coarse powder is 300-400 mesh; The D97 of the ultrafine heavy calcium carbonate powder is 2 to 2.5 μm.
6. The method for preparing the modified composite light calcium carbonate according to claim 5, characterized in that: The solid content of the calcium carbonate slurry is 60-70%; The amount of silicon source added is 20-30% of the mass of the calcium carbonate coarse powder; The addition amount of the pre-dispersant is 0.5-0.8% of the mass of the calcium carbonate coarse powder, and the mass ratio of part of the pre-dispersant to the remaining pre-dispersant is 0.6-0.8:0.2-0.
4.
7. The method for preparing the modified composite light calcium carbonate according to claim 6, characterized in that: The pre-dispersant includes sodium alkyl diphenyl ether sulfonate and / or sodium fatty alcohol polyoxyethylene ether sulfate; The silicon source is sodium silicate and / or potassium silicate.
8. The method for preparing the modified composite light calcium carbonate according to claim 6 or 7, characterized in that: The mass ratio of the light calcium carbonate powder to the ultrafine heavy calcium carbonate powder is 6-8:2-4; The addition amount of the composite modifier accounts for 0.8-1.2% of the total mass of the light calcium carbonate powder and the ultrafine heavy calcium carbonate powder; The composite modifier is obtained by compounding vinyl-terminated silicone oil and silane coupling agent KH560, wherein the addition amount of vinyl-terminated silicone oil is 0.5-0.8% of the total mass of light calcium carbonate powder and ultrafine heavy calcium carbonate powder, and the addition amount of silane coupling agent KH560 is 0.3-0.5% of the total mass of light calcium carbonate powder and ultrafine heavy calcium carbonate powder; The modification temperature is 100-120° C., and the modification time is 30-50 minutes.
9. A modified composite light calcium carbonate prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the modified composite light calcium carbonate according to claim 9 in preparing wear-resistant rubber, characterized in that: 100 parts of natural rubber, 3-7 parts of zinc oxide, 1-3 parts of stearic acid, 1-3 parts of sulfur, 1-3 parts of accelerator DM, 40-60 parts of the modified composite light calcium carbonate described in claim 9, 0.1-1 parts of accelerator TMTD, 1-3 parts of silane coupling agent Si-69, 1-3 parts of plasticizer DOP, 1-5 parts of antioxidant RD and 3-8 parts of white carbon black are mixed, and kneaded at 50-70° C. for 10-30 minutes to obtain a wear-resistant rubber.
Citation Information
Patent Citations
Method for preparing composite calcium carbonate
CN107446384A
Preparation method of special nano calcium carbonate for rubber
CN109911925A
Superfine ground calcium carbonate for wear-resistant rubber and preparation method and application of superfine ground calcium carbonate
CN111808439A
Superfine calcium carbonate filler for PVC (polyvinyl chloride) cable as well as preparation method and application of superfine calcium carbonate filler
CN116396533A
Cited By
Preparation method and application of heavy calcium carbonate powder with high oil absorption value
CN120665456A